2012
DOI: 10.1371/journal.ppat.1002713
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Superoxide Dismutase Protects Histoplasma Yeast Cells from Host-Derived Oxidative Stress

Abstract: In order to establish infections within the mammalian host, pathogens must protect themselves against toxic reactive oxygen species produced by phagocytes of the immune system. The fungal pathogen Histoplasma capsulatum infects both neutrophils and macrophages but the mechanisms enabling Histoplasma yeasts to survive in these phagocytes have not been fully elucidated. We show that Histoplasma yeasts produce a superoxide dismutase (Sod3) and direct it to the extracellular environment via N-terminal and C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
172
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(177 citation statements)
references
References 71 publications
5
172
0
Order By: Relevance
“…Superoxide dismutase (SOD, EC 1.15.1.1) is present in all living organisms that efficiently transform superoxide (O 2 -) into hydrogen peroxide (H 2 O 2 ) and molecular oxygen [4]. Superoxide dismutases are well described in prokaryotic and eukaryotic cells and have proven to be universal protective tools that protect the cell from damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Superoxide dismutase (SOD, EC 1.15.1.1) is present in all living organisms that efficiently transform superoxide (O 2 -) into hydrogen peroxide (H 2 O 2 ) and molecular oxygen [4]. Superoxide dismutases are well described in prokaryotic and eukaryotic cells and have proven to be universal protective tools that protect the cell from damage [5].…”
Section: Introductionmentioning
confidence: 99%
“…These findings support a model in which oxidative damage to biomolecules in the SOD mutants is superoxide-driven and is due mainly to iron release from the 4Fe-4S clusters. Moreover, SODs participate in the OSR and are associated with virulence in fungal pathogens like C. albicans or H. capsulatum (Hwang et al, 2002;Youseff et al, 2012). In this paper, we expand our knowledge about the roles of the superoxide dismutases in C. glabrata.…”
Section: Discussionmentioning
confidence: 87%
“…8). This is surprising since previous observations have proposed SODs as virulence factors in bacteria and pathogenic yeasts (Hwang et al, 2002;Langford et al, 2002;Narasipura et al, 2003;Youseff et al, 2012). This evidence indicates that there are additional factors that compensate for the lack of SODs in vivo.…”
Section: Glabrata Sods Are Dispensable For Colonization In a Murinmentioning
confidence: 81%
See 1 more Smart Citation
“…Fungi have evolved effective antioxidant mechanisms that include enzyme families that act as ROS scavengers. Previous studies have shown members of antioxidant enzymes families such as SODs and CATs may have complementary effects during the cellular developmental processes (Xie et al ., 2012; Youseff et al ., 2012; Wang et al ., 2013; Zhang and Feng, 2018). Our investigations confirmed that antioxidant enzyme genes cat1 , sod1 , cat2 and sod2 had different expressions during conidia development in M. rileyi (Fig.…”
Section: Discussionmentioning
confidence: 99%